UMP graduates selected to pioneer aerospace industry - UMP, PNC
Three graduates from Universiti Malaysia Pahang’s (UMP) Faculty of Mechanical Engineering (FKM) were among the 24 candidates who secured their seats in the “Aerospace Leaders” pilot programme, successfully beating thousands of other contenders in the nationwide search.